Management of a Transcranial Abscess Secondary to Interleukin-1 Receptor Associated Kinase 4 Deficiency. Issue 1 (January 2015) - Pidgeon, Thomas Edward; Ahmad, Fateh; Hackett, Scott; Rodrigues, Desiderio; Nishikawa, Hiroshi
<x xml:space="preserve">Abstract</x> Abstract Interleukin-1 receptor associated kinase 4 (IRAK-4) deficiency is a primary immunodeficiency that predisposes to opportunistic pyogenic infections in affected patients. The presentation can be variable, and the microbiological and immunologic management of this condition has been documented; however, the atypical nature of its presentation calls for a different approach in its surgical management. This is the first reported case of transcranial progression of a soft tissue abscess in a patient with IRAK-4 deficiency, with an emphasis on a multidisciplinary approach to treat infection at an extremely vulnerable anatomic site.